Genetic Variability Trend of Lusitano Horse Breed Reared in Italy - Maria Cristina Cozzi; Paolo Valiati; Maria Longeri; Carlos Ferreira; Sofia Abreu Ferreira (Animals, 2022)
The Lusitano Horse (LH) originates from Portugal, but is reared worldwide. Since 1994, the University of Milan has routinely tested the LHs bred in Italy for parentage control. This study aims to assess the genetic variability of the LH reared in Italy using 16 microsatellites markers. Moreover, the genetic variability changes over the years in the total population (n.384) and in unrelated horses (n.47) were evaluated. Horses were grouped according to their date of birth (1975–1990, 1991–2000, 2001–2010, 2010–2019). Standard genetic diversity parameters, including observed (Ho) and expected (He) heterozygosity, Hardy-Weinberg equilibrium (HWE; P-Val), allelic richness, and inbreeding coefficient (Fis) were estimated. In the whole period, the total population showed Ho as high as 0.69, low Fis (0.057), and imbalance for HWE. When considering the unrelated horses, Ho was seen to increase over time (from 0.594 in 1975–1990 to 0.68 in 2010–2019) and frequencies were in HWE, again having low and decreasing values of Fis (from 0.208 in 1975–1990 to 0.019 in 2010–2019). Bottleneck analysis excluded a recent population decline. Principal Coordinate Analysis at the individual level defined two clusters, the major cluster including all the most recent horses. An increasing number of dams (156% more from 2001–2010 to 2011–2019) supports the good variability recorded in the population so far. However, the high number of foals (77.2%) sired by only four stallions in recent years suggests caution in the choice of the sires for the future.